2022
DOI: 10.1021/acs.jpcc.1c10521
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crystal Structure, Encapsulation, and Annealing on Photochromism in Nd Oxyhydride Thin Films

Abstract: Thin films of rare earth metal oxyhydrides show a photochromic effect, the precise mechanism of which is yet unknown. Here, we made thin films of NdH 3–2 x O x and show that we can change the band gap, crystal structure, and photochromic contrast by tuning the composition (O 2– :H – ) via the sputtering deposition pressure. To protect these films from rapid oxidation, we add a thin ALD coating of Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Ca-doped yttrium oxyhydride thin films ((Ca z Y 1– z )H x O y , ∼ 300 nm) were prepared by reactive magnetron cosputtering of Ca (MaTecK, 99.9%) and Y (Stanford, 99.99%) metal targets onto 10 × 10 mm 2 quartz plates (MaTecK) at room temperature (∼21 °C) and an Ar/H 2 (7:1 flow) atmosphere. Following from our previous work on REH 3–2 x O x thin films (RE = Sc, Y, Nd, Gd, Dy, and Er), 2 5 the combined Ar/H 2 deposition pressure ( p dep ) affects the as-deposited RE dihydride; we found that if p dep is below a critical pressure ( p * ∼ 0.4 Pa for Y), 2 , 4 the film remains a metallic RE dihydride, but above p *, it forms a semiconducting oxyhydride upon ambient air exposure ( Figure 1 ). Similarly, we find that upon air exposure the as-deposited CaY hydride films become semiconducting, although some of the films already seem to incorporate oxygen when measured in the glovebox before air exposure (glovebox: [H 2 O] and [O 2 ] < 0.1 ppm), perhaps due to oxidation from residual gases.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca-doped yttrium oxyhydride thin films ((Ca z Y 1– z )H x O y , ∼ 300 nm) were prepared by reactive magnetron cosputtering of Ca (MaTecK, 99.9%) and Y (Stanford, 99.99%) metal targets onto 10 × 10 mm 2 quartz plates (MaTecK) at room temperature (∼21 °C) and an Ar/H 2 (7:1 flow) atmosphere. Following from our previous work on REH 3–2 x O x thin films (RE = Sc, Y, Nd, Gd, Dy, and Er), 2 5 the combined Ar/H 2 deposition pressure ( p dep ) affects the as-deposited RE dihydride; we found that if p dep is below a critical pressure ( p * ∼ 0.4 Pa for Y), 2 , 4 the film remains a metallic RE dihydride, but above p *, it forms a semiconducting oxyhydride upon ambient air exposure ( Figure 1 ). Similarly, we find that upon air exposure the as-deposited CaY hydride films become semiconducting, although some of the films already seem to incorporate oxygen when measured in the glovebox before air exposure (glovebox: [H 2 O] and [O 2 ] < 0.1 ppm), perhaps due to oxidation from residual gases.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Rare-earth metal oxyhydrides (REH 3–2 x O x ) are multianion compounds which have gained attention in recent years because they exhibit a photochromic effect . Thin films of REH 3–2 x O x (RE = Sc, Y, Nd, Gd, Dy, and Er) are transparent semiconductors which “darken”, or become opaque, upon exposure to light with photon energy greater than their band gap ( E incident > E g ). When this light is removed, the materials return to their transparent state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaykina. et al enhanced the stability of NdO x H y by adding an alumina protective layer via ALD (atomic layer deposition), but the surface encapsulation layer enhanced the bleaching kinetics of the films [ 20 ]. Lu et al improved the generation energy of nanocrystals by doping Sr into CsPbI 3 nanocrystals, replacing Pb to cause a slight lattice shrinkage, and the environmental stability was enhanced [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Photochromism and photo-conductivity in polycrystalline rare-earth oxyhydride thin films were first reported in 2011 on Y-based compounds. [5] Since then, several other REs (RE=Sc, Y, Nd, Sm, Gd, Dy, Er) [6][7][8][9][10] were found to form photochromic oxyhydride thin films, suggesting that these properties are rather general to the whole material class. Common to all of them is the REO x H 3 − 2x composition and a crystal structure based on the CaF 2 -type lattice.…”
Section: Introductionmentioning
confidence: 99%